Очень срочно, ответ присылайте в Иде фотографии, потому что по-другому я не пойму, спасибо!)
Очень срочно, ответ присылайте в Иде фотографии, потому что по-другому я не пойму, спасибо!)
Ответ(ы) на вопрос:
х³-8=(х-2)·(х²+2х+4)
[latex] \frac{1}{x-2} - \frac{12}{(x-2)(x^2+2x+4)} - \frac{2}{x^2+2x+4}= \frac{x^2+2x+4-12-2\cdot(x-2)}{(x-2)(x^2+2x+4)}= \\ \\ =\frac{x^2+4-12-2\cdot(-2)}{(x-2)(x^2+2x+4)}= \frac{x^2-4}{(x-2)(x^2+2x+4)}= \frac{(x-2)(x+2)}{(x-2)(x^2+2x+4)}= \frac{x+2}{x^2+2x+4} [/latex]
Не нашли ответ?
Похожие вопросы